Predictors of seizure‐free outcome after epilepsy surgery for pediatric tuberous sclerosis complex. Issue 11 (30th September 2013) - Krsek, Pavel; Jahodova, Alena; Kyncl, Martin; Kudr, Martin; Komarek, Vladimir; Jezdik, Petr; Jayakar, Prasanna; Miller, Ian; Korman, Brandon; Rey, Gustavo; Resnick, Trevor; Duchowny, Michael
Summary: Purpose: Variable predictors of postsurgical seizure outcome have been reported in children with tuberous sclerosis complex (TSC). We analyzed a large surgical series of pediatric TSC patients in order to identify prognostic factors crucial for selection of subjects for epilepsy surgery. Methods: Thirty‐three children with TSC who underwent excisional epilepsy surgery at Miami Children's Hospital were retrospectively reviewed. A total of 29 clinical, neuropsychological, electroencephalography (EEG), magnetic resonance imaging (MRI), and surgical variables were analyzed and related to seizure outcomes. Univariate Barnard's exact test, Wilcoxon's rank‐sum test, and multivariate statistical Cox's model were used to examine the significance of associations between the variables and seizure outcome. Key Findings: Eighteen patients (55%) have been seizure‐free 2 years after (final) surgery; postoperative complications occurred in five subjects (15%). Complete removal of epileptogenic tissue detected by both MRI and intracranial EEG, regional scalp interictal EEG patterns, and agreement of interictal and ictal EEG localization were the most powerful predictors of seizure‐free outcome. Other significant predictors included occurrence of regional scalp ictal EEG patterns, fewer brain regions affected by tubers, presence of preoperative hemiparesis, and one‐stage surgery. Remaining factors such as age at seizure onset, incidence of infantile spasms or other seizure types, duration of epilepsy, seizure frequency, mental retardation, as well as types and extent of resections did not influence outcome. Significance: Perioperative features rather than preoperative variables are the most important determinants of postsurgical seizure outcome in patients with TSC. Our findings may assist in the surgical management of these patients.